Faktor Penyebab Illegal Logging dan Cara Pencegahannya di Kawasan Hutan Jati Nenuk (Studi Kasus Hutan Produksi di Desa/Kelurahan Naekasa, Kecamatan Tasifeto Barat, Kabupaten Belu) - Stefania Santy Sirik; Ludji Michael Riwu Kaho; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Nenuk Teak Forest Area is one of the areas that has experienced changes caused by deforestation in the form of illegal logging by communities around the forest area. This study aims to determine the factors that cause illegal logging and what methods are used tp prevent illegal logging in the Nenuk Teak Forest Area, Naekasa Villge, Tasifeto Barat District, East Belu. The method used is qualitative with a case study design. The sampling technique for illegal logging communities uses the snowball sampling technique, while the management of the Nenuk Teak Forest Area uses purposive sampling. Data collection was carried out through interview, observation, and documentation. The instrument used was an in-depth interview guide. Data analysis using qualitative. The research results show that there are 6 factors that cause illegal logging (economy and poverty, road accces to the forest, market demand, lack of supervision and law enforcement, limited employment alternatives, as well as ineffective policies), and there are 5 ways to prevent illegal logging carried out by KPH (increasing public awareness, strict law enforcement, inter-agency cooperation, sustainable forest certification and management, and reforestation and forest rehabilitation.